5(x-3)+1=6x-2

Simple and best practice solution for 5(x-3)+1=6x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-3)+1=6x-2 equation:



5(x-3)+1=6x-2
We move all terms to the left:
5(x-3)+1-(6x-2)=0
We multiply parentheses
5x-(6x-2)-15+1=0
We get rid of parentheses
5x-6x+2-15+1=0
We add all the numbers together, and all the variables
-1x-12=0
We move all terms containing x to the left, all other terms to the right
-x=12
x=12/-1
x=-12

See similar equations:

| -2p=4.8 | | -6(r+6)=-84 | | 23+v/19=-4 | | 247=19x | | 22=8x+4-2x | | 9x-15+6x-15=180 | | x−4(2x+6)=5−7x | | 3c-4c=48 | | 85x=-15 | | 4(-2f-3)/11=4 | | 3(3-2x)+2(x+1)=10 | | 7=f+3 | | -2+7p=1+8p | | -6+3(8x-6)=22+8x | | 3n*500=1300 | | a-17=-3 | | 29=9x=4=4x | | 3.6=5.5n-5.7n+1.6 | | -7x+3(2-4x)=6+8x | | -4x+3x=-3x+x+5 | | a-17=3 | | 23-6x=-5(8-3x) | | 15=1.5r+3. | | 9x+1=(2x-7) | | (5/4)p=(4/3)p+(5/2) | | -13+8x=2+10x+5 | | 1x=x+16 | | -3(x+2)=-4x+5 | | 4p-5-2=-11 | | -6x-2+3=-35 | | -47=7g-1 | | 3(g−15)=6 |

Equations solver categories